TelePain: Primary care chronic pain management through weekly didactic and case‐based telementoring - Diane M. Flynn; Linda H. Eaton; Honor McQuinn; Ashley Alden; Alexa R. Meins; Tessa Rue; David J. Tauben; Ardith Z. Doorenbos (Contemporary Clinical Trials Communications, 2017)
Chronic pain is a significant problem among military personnel and a priority of the military health system. The U.S. Army Surgeon General's Pain Management Task Force recommends using telehealth capabilities to enhance pain management. This article describes the development and evaluation of a telehealth intervention (TelePain) designed to improve access to pain specialist consultation in the military health system. The study uses a wait-list cluster controlled clinical trial to test: 1) effectiveness of the intervention, and 2) interviews to assess barriers and facilitators of the intervention implementation. The intervention involves a didactic presentation based on the Joint Pain Education Curriculum followed by patient case presentations and multi-disciplinary discussion via videoconference by clinicians working in the military health system. A panel of pain specialists representing pain medicine, internal medicine, anesthesiology, rehabilitation medicine, psychiatry, addiction medicine, health psychology, pharmacology, nursing, and complementary and integrative pain management provide pain management recommendations for each patient case. We use the Pain Assessment Screening Tool and Outcomes Registry (PASTOR) to measure patient outcomes, including pain, sleep, fatigue, anxiety, and depression. This article reports some of the challenges and lessons learned during early implementation of the TelePain intervention. Weekly telephone meetings among the multisite research team were instrumental in problem solving, identifying problem areas, and developing solutions. Solutions for recruitment challenges included additional outreach and networking to military health providers, both building on existing relationships and new relationships.